High-Temperature Precipitation Design-of-Experiments Simulation in Low-Alloy Cr–Mo–Ni Hot Forging Steel - Roberto Gonzalez-Ojeda; Octavio Lozada-Flores; Gonzalo Gonzalez-Reyes; Jose Manuel Sanchez-Moreno (Metals, 2021)
The role of alloying elements such as Cr, Mo and Mn on low-alloy 8620 steel during hot forging operations is not yet clear, as, during deformation in the 1000~1100 °C temperature range, the austenite grain size remains small, ensuring the capacity of the forged part to be subsequently modified by surface hardening procedures. This work analyzed a deformed bar considering hardness at different geometry zones, along with SEM and TEM microstructures of previous austenite grains and lamellar martensite spacing. Moreover, Thermocalc simulations of M7C3, M23C6 and MnS precipitation were combined with Design of Experiments (DOE) in order to detect the sensitivity and significant variables. The values of the alloying elements’ percentages were drastically modified, as nominal values did not produce precipitation, and segregation at the austenite matrix may have been responsible for short-term, nanometric precipitates producing grain growth inhibition.